The nitrogen content of the tomato leaf apoplast increases during infection by Cladosporium fulvum - Solomon, P.; Oliver, Richard (2001)
To address the problem of the nutritional requirements of phyto-pathogenic fungi growing in planta, the environment for the intercellular biotrophic pathogen, Cladosporium fulvum Cooke, of tomato (Lycopersicon esculentum Mill.) was analysed. Using a novel technique for infiltrating the intercellular space, we measured the concentrations of 21 amino acids, nitrate and ammonia in the apoplast of the tomato leaf during infection. The concentrations of most amino acids, and total nitrogen content, increased during infection. The levels of nearly all amino acids remained relatively unchanged during an incompatible interaction. All protein amino acids were detected during infection, except cysteine and tryptophan. Most amino acids were present at a concentration between 0.1-0.7 mM. The non-protein amino acid %-aminobutyric acid was detected at the highest concentration (up to 2.5 mM) during the compatible interaction. Preliminary investigations on the source of the amino acids revealed that protease activity within the apoplast increased during infection and that infection induced the expression of the pathogenicity-related extracellular serine protease P69B. The nitrogen status of the infecting fungus and sources for the additional amino acids are discussed.